Periodic limb movements in patients with obstructive sleep apnea syndrome - Xiaobo Zhou (Nature Portfolio, 2021)
Abstract The aim of the study was to assess the factors associated with periodic limb movements during sleep (PLMS) among obstructive sleep apnea syndrome (OSAS) patients and identify the role of PLMS in patients with OSAS. 303 adult patients with OSAS were included in the study. All patients completed physical examination, Epworth sleepiness scale (ESS), and polysomnography. Diagnosis of PLMS was made if the periodic leg movements index (PLMI) was ≥ 15. Chi-square test, ANOVA, univariate and multivariate logistic regression analyses were conducted to identify factors associated with PLMS among OSAS patients. Statistical analyses were performed with SPSS 26.0 for mac. Statistically significant difference was considered if P value < 0 .05. Among the 303 adult patients with OSAS, 98 patients had significant PLMS and the other 205 had no significant PLMS. Compared with OSAS patients without PLMS, OSAS patient with PLMS were older, had shorter REM duration and greater apnea–hypopnea index (AHI) (P < 0.05). The study suggests that PLMS is a matter of concern among patients with OSAS. A better understanding of the role of PLMS among OSAS patients could be useful in better recognition, intervention and treatment of OSAS.